Ultrasound imaging of the posterior lateral corner of the knee: a pictorial review of anatomy and pathologies - Wu, Wei-Ting; Onishi, Kentaro; Mezian, Kamal; Naňka, Ondřej; Wang, Bow; Su, Daniel Chiung-Jui; Ricci, Vincenzo; Chang, Ke-Vin; Özçakar, Levent (Insights into imaging, 2024)
Assessment of the posterior lateral knee pain poses diagnostic challenges, requiring accurate evaluation of various structures in light of the medical history and physical examination. Despite substantial progress in the ultrasonographic diagnosis of musculoskeletal disorders, the current protocol (EURO-MUSCULUS/USPRM. Basic scanning protocols for knee) fails to conduct a comprehensive investigation into the intricate, tendons, and ligaments of the posterior lateral knee. This pictorial review aims to bridge this gap by offering a systematic approach to utilize ultrasound examination of the less-discussed structures in this specific region. Providing cadaveric and magnetic resonance images, this essay demonstrates the efficacy of ultrasound in diagnosing posterior lateral knee pain. Notably, pathologies such as ligamentous sprains and tears are clearly discernible. Moreover, the integration of ultrasound guidance plays a vital role in reducing the risk of inadvertent neurovascular injury during injection, such as the common peroneal nerve and lateral genicular artery. This comprehensive approach will enhance clinicians' understanding and equip them with effective management strategies for posterior lateral knee pain.Critical relevance statement In this visual exposition, we delve into the intricacies of the posterior lateral corner of the knee. Offering a methodical approach to employ ultrasound for visualization of the less-explored structures within this region, the authors aim to enhance the diagnosis in posterior lateral knee pain.Key points1. Ultrasound excels at revealing intricate structures in the posterior lateral knee.2. Due to proximity of vital structures, extreme caution is crucial during injections.3. Employing dynamic scan and understanding ligaments enables a comprehensive exploration of pathologies.